2021
DOI: 10.1186/s13068-021-02057-y
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9-mediated genome editing directed by a 5S rRNA–tRNAGly hybrid promoter in the thermophilic filamentous fungus Humicola insolens

Abstract: Background Humicola insolens is a filamentous fungus with high potential of producing neutral and heat- and alkali-resistant cellulase. However, the genetic engineering tools, particularly the genome-editing tool, are scarce, hindering the study of cellulase expression regulation in this organism. Results Herein, a CRISPR/Cas9 genome-editing system was established in H. insolens based on a hybrid 5S rRNA–tRNAGly promoter. This system is superior to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 71 publications
0
1
0
Order By: Relevance
“…2B). Similarly, during CRISPR/Cas mediated gene editing of the thermophilic fungus H. insolens, Fan and coworkers [21] have also reported frame-shift mutations upstream of the PAM site involving either a single nucleotide deletion or insertion.…”
Section: Crispr/cas9 Mediated Gene Disruption In Thermophilic R Emers...mentioning
confidence: 91%
See 1 more Smart Citation
“…2B). Similarly, during CRISPR/Cas mediated gene editing of the thermophilic fungus H. insolens, Fan and coworkers [21] have also reported frame-shift mutations upstream of the PAM site involving either a single nucleotide deletion or insertion.…”
Section: Crispr/cas9 Mediated Gene Disruption In Thermophilic R Emers...mentioning
confidence: 91%
“…In another report, three cytosine base editors (CBEs; Mtevo-BE4max, MtGAM-BE4max, and Mtevo-CDA1) in M. thermophila were used for gene inactivation by precisely changing three codons (CAA, CAG, and CGA) into stop codons without the production of DSBs [20]. In H. insolens, a hybrid 5S rRNA-tRNA Gly promoter based CRISPR/Cas9 based disruption of pigment synthesis gene pks and the transcription factor xyr1 gene was developed [21], demonstrating the significance of CRISPR technology in genetic engineering of thermophilic fungi.…”
Section: Introductionmentioning
confidence: 99%
“…(2013) demonstrated that CRISPR/Cas9-mediated genome editing could be applied to Saccharomyces cerevisiae ( 17 ), the approach was quickly introduced into a number of filamentous fungi including Trichoderma reesei ( 18 ), Neurospora crassa ( 19 ), a number of Aspergillus species ( 20 ) and Penicillium chrysogenum ( 21 ). Up to date, the CRISPR-Cas9 genome-editing methods have been established in >40 fungal species ( 12 , 22 , 23 ), and most of them were conducted using a single-guide ribonucleic acid (sgRNA) and Cas9 to introduce a DNA double-strand break into the target sequence and donor DNA with homology arms to introduce the desired genetic change ( 12 ). In contrast to other Aspergillus species, relatively few genetic manipulation methods have been established for A. terreus research.…”
Section: Introductionmentioning
confidence: 99%